Strategy to Improve Exclusive Breastfeeding Coverage Through Optimizing the Role of Posyandu Cadres in the Working Area of Sibande Community Health Center, Pakpak Bharat Regency, 2025 - Syafrida Eriyanti; Rahmad Gurusinga; Desideria Yosepha Ginting (JURNAL KESMAS DAN GIZI (JKG), 2026)
Exclusive breastfeeding during the first six months of life is an important indicator of maternal and infant health. However, the coverage of exclusive breastfeeding in the working area of the Sibande Community Health Center, Pakpak Bharat Regency, is still not optimal. One of the factors contributing to the improvement of exclusive breastfeeding coverage is the role of Posyandu cadres as the frontline of community-based health services. This study aims to describe the role of Posyandu cadres, identify the obstacles they face, and formulate strategies to improve exclusive breastfeeding coverage through the optimization of the role of Posyandu cadres. This study employed a qualitative approach with a phenomenological study design. Informants were selected purposively and consisted of 12 participants, including Posyandu cadres, breastfeeding mothers with infants aged 0–6 months, and health workers from the Sibande Community Health Center. Data were collected through in-depth interviews, observation, and documentation studies, and were subsequently analyzed using thematic analysis. The results showed that Posyandu cadres play roles as educators, motivators, companions, and intermediaries between breastfeeding mothers and health workers. However, these roles have not been performed optimally due to limited knowledge and counseling skills related to breastfeeding, the influence of local cultural practices, and the lack of continuous guidance and support. The discussion indicates that optimizing the role of cadres through exclusive breastfeeding counseling training, continuous mentoring, the provision of educational media, and strengthened cross-sector coordination has the potential to improve exclusive breastfeeding coverage. The conclusion of this study highlights that optimizing the role of Posyandu cadres is an important strategy for increasing exclusive breastfeeding coverage. It is recommended that the Community Health Center regularly conduct exclusive breastfeeding counseling training and strengthen supervision and support for Posyandu cadres.